Prioritizing the health education needs based on community participation: AHP method - Masoumeh Hashemian; Fatemeh Ghardashi; A R Izadi; Roya Akbarzadeh (Wolters Kluwer Medknow Publications, 2019)
INTRODUCTION: The identification of health education needs through the community results in targeted services and health promotion. Prioritizing these needs, in addition to identifying the desired health system based on the needs of the community, is required for the optimal allocation of resources. Therefore, this study was conducted with the aim prioritizing the health educational needs of Sabzevar-Iran community. MATERIALS AND METHODS: This study was a two-step mix study. In the first stage, the qualitative method of the main themes of health educational needs of Sabzevar society was determined. Then, the questionnaire was prepared by a paired scale (36 questions) and quantitative method was used to prioritize the main themes with Analytic Hierarchy Process (AHP) software. The random sampling method was used in this study and data analysis was performed using Expert Choice software using AHP method. RESULTS: Social problems with 0.206, contagious diseases with 0.205, nutrition with 0.161, and public health with 0.132 were in the first to fourth grades of health educational needs in Sabzevar city and environmental health, health management, noncontagion diseases, elderly, and occupational health were in the fifth to ninth grades. The consistency index in this study was 0.08, although the adjustment index is <0.1 good and acceptable. CONCLUSION: Social problems are the first priority of Sabzevar society, which require appropriate training.